PENINGKATAN KETERAMPILAN MANAJEMEN USAHA BAGI MAHASISWA KEPERAWATAN MELALUI PELATIHAN KEWIRAUSAHAAN - Siti Maryati (Universitas Muhammadiyah Semarang, 2015)
Background The problems experienced as a manager of health education that the number of nursing graduates from vocational education to master reaches 24000-25000 people per year. The low absorption of graduate nursing education and the limited employment opportunities for nurses in government institutions. It would need to nurse provided the ability / skill other in order to open up business opportunities independently or collaborating entrepreneur's ability to do since I was a student and when it's completed education. How to Troubleshooting, efforts to equip abilities / skills of nurses do entrepreneurs by giving lectures on entrepreneurship and giving Entrepreneurship Training. This activity aims to provide skills of nurses in the management of care services in the